A snapshot of virological presentation and outcome of immunosuppression‐driven HBV reactivation from real clinical practice: Evidence of a relevant risk of death and evolution from silent to chronic infection. Issue 7 (14th May 2019) - Salpini, Romina; Battisti, Arianna; Colagrossi, Luna; Di Carlo, Domenico; Fabeni, Lavinia; Piermatteo, Lorenzo; Cerva, Carlotta; Lichtner, Miriam; Mastroianni, Claudio; Marignani, Massimo; Maylin, Sarah; Delaugerre, Constance; et al.
Abstract: The study was undertaken in order to provide a snapshot from real clinical practice of virological presentation and outcome of patients developing immunosuppression‐driven HBV reactivation. Seventy patients with HBV reactivation were included (66.2% treated with rituximab, 10% with corticosteroids and 23.8% with other immunosuppressive drugs). Following HBV reactivation, patients received anti‐HBV treatment for a median (IQR) follow‐up of 31(13‐47) months. At baseline‐screening, 72.9% of patients were HBsAg‐negative and 27.1% HBsAg‐positive. About 71.4% had a diagnosis of biochemical reactivation [median (IQR) HBV DNA and ALT: 6.9 (5.4‐7.8) log IU/mL and 359 (102‐775) U/L]. Moreover, 10% of patients died from hepatic failure. Antiviral prophylaxis was documented in 57.9% and 15.7% of HBsAg‐positive and HBsAg‐negative patients at baseline‐screening (median [IQR] prophylaxis duration: 24[15‐33] and 25[17‐36] months, respectively). Notably, HBV reactivation occurred 2‐24 months after completing the recommended course of anti‐HBV prophylaxis in 35.3% of patients. By analysing treatment outcome, the cumulative probability of ALT normalization and of virological suppression was 97% and 69%, respectively. Nevertheless, in patients negative to HBsAg at baseline‐screening, only 27% returned to HBsAg‐negative status during prolonged follow‐up, suggesting the establishment of chronic infection. In conclusion, most patients received a diagnosis of HBV reactivation accompanied by high ALT and 10% died for hepatic failure, supporting the importance of strict monitoring for an early HBV reactivation diagnosis. Furthermore, HBV reactivation correlates with high risk of HBV chronicity in patients negative for HBsAg at baseline‐screening, converting a silent into a chronic infection, requiring long‐term antiviral treatment. Finally, a relevant proportion of patients experienced HBV reactivation after completing the recommended course of anti‐HBV prophylaxis, suggesting the need to reconsider proper duration of prophylaxis particularly in profound immunosuppression.